Association of adherence measured by self-reported pill count with achieved blood pressure level in hypertension patients: a cross-sectional study - Iin Ernawati; Eziah Ika Lubada; Ria Lusiyani; Rahmad Aji Prasetya (BMC, 2022)
Abstract Background Medication adherence plays an essential role in controlling blood pressure to reduce morbidity and mortality of hypertension disease. Thus, this study aimed to determine the association of medication adherence measured by self-reported pill count with blood pressure levels among patients at several community health centers in Surabaya. Methods Adherence was assessed using the pill count method by comparing the total number of antihypertension drugs taken with the prescribed drugs. The inclusion criteria involved hypertensive patients who received antihypertension drugs, specifically adults and elderly, except the pregnant woman. The patient blood pressure was measured by healthcare workers in the targeted community health centers. Descriptive and multivariable logistic regression analyses were performed to assess factors associated with medication adherence with blood pressure levels. Results A total of 264 hypertensive outpatients participating in this study, 77.65% of participants were adherent to antihypertensive drugs based on the pill count method, and 40.91% of participants had controlled blood pressure. Patients with uncontrolled blood pressure were about six times (adjusted odds ratio [AOR]: 6.15; 95% confidence interval [CI]: 2.694-14.039; P = 0.000) more likely to have non-adherent medication than patients with controlled blood pressure. Reciprocally, non-adherent participants (pill count < 80%) were about six times (AOR: 6.081; 95% CI: 2.672-13.838; P = 0.000) more likely to have uncontrolled blood pressure compared to adherent patients (pill count ≥ 80%). Age less than 40 years old (AOR: 5.814; 95% CI: 1.519-22.252; P = 0.01) and having middle school educational level (AOR: 0.387; 95% CI: 0.153-0.974; P = 0.045) were found to be independent factors associated with uncontrolled blood pressure. Conclusions The result showed that non-adherence to antihypertension drugs is associated with uncontrolled blood pressure. Then, age could be associated with uncontrolled blood pressure. Thus, pharmacists and other healthcare providers should pay attention to improving medication adherence and maintaining the controlled blood pressure.